Fluidics Thrust Vectoring Using Co-Flow Method - Al-Asady, Ali Abdul Almuhsen; Abdullah, Ahmed Mujahid (Al-Nahrain Journal for Engineering Sciences, 2017)
Computational and experimental investigations of thrust vectoring using co flow method had been carried in the present work. The experimental investigation included design and construction of rig with rectangular duct with aspect ratio (4.4) in order to investigate the effect of various geometric variables on thrust vectoring angle. Set of experiments tests carried out over the mass flow ratio ( ) range 0 ? ? 0.23, gap height h/H= (0.0294, 0.0588, 0.088 and 0.1176) and coanda surface diameter ?/H= (1.176, 2.353 and 3.529). _x000D_ Load measurements were obtained using four load cells. The computational investigation involved a 3D numerical solution by FLUENT 6.3.26 Software for some of experimental cases. The results show that the increase in secondary jet blowing rate lead to increase the jet vectoring angle, there are three zone can be observed, dead zone appears at low mass flow ratios, then followed by control region in which continuous thrust vector control can be achieved followed by a saturation region. The coanda surface diameter determines the length of the dead zone, which a small coanda surface used for coanda effect resulted in a prolonged dead zone range and the secondary gap height to the primary gap height had inverse relation with jet vectoring angle. The investigation shows that both the experimental and computational results obtained follow a similar trend line.